Assessment of Melatonin-Cultured Collagen/Chitosan Scaffolds Cross-Linked by a Glyoxal Solution as Biomaterials for Wound Healing - Beata Kaczmarek-Szczepańska; Judith M. Pin; Lidia Zasada; Mauritz M. Sonne; Russel J. Reiter; Andrzej T. Slominski; Kerstin Steinbrink; Konrad Kleszczyński (MDPI AG, 2022)
Chitosan (CTS) and collagen (Coll) are natural biomaterials that have been extensively used in tissue engineering or wound healing applications, either separately or as composite materials. Most methods to fabricate CTS/Coll matrices employ chemical crosslinking to obtain solid and stable scaffolds with the necessary porosity and mechanical properties to facilitate regeneration. In this study, we comparatively assessed the physicochemical properties of 3D scaffolds loaded with a cross-linker, glyoxal. Using a scanning electron microscope, we evaluated the microstructure of resultant matrices and their mechanistic testing by the determination of the compressive modulus (Emod), the maximum force (Fmax), thermogravimetric analysis (TG), Fourier Transform Infrared Spectroscopy-Attenuated Total Reflectance (FTIR-ATR), and proliferation rate in vitro using human epidermal keratinocytes and dermal fibroblasts cultured in presence of melatonin solution (10−5 M). We observed that enhanced content of collagen (50CTS/50Coll or 20CTS/80Coll compared to 80CTS/20Coll) significantly elevated the physicochemical capacities of resultant materials. Besides, presence of 5% glyoxal increased porosity, Emod and Fmax, compared to scaffolds without glyoxal. Finally, keratinocytes and dermal fibroblasts cultured on subjected matrices in presence of melatonin revealed a prominently enhanced growth rate. This indicates that the combination of glyoxal and melatonin make it imperative to consider these materials as a promising approach for targeting skin tissue engineering or regenerative dermatology.